Gender Differences in Nicotine Induced Dyslipidemia and Hyperglycemia in Mice - Samina Bano; Shabana Saeed (Journal of Basic & Applied Sciences, 2021)
The purpose of this study is to examine the prevalence of metabolic syndrome in nicotine treated male and female mice and to evaluate gender related differences. For these purposes adult male and female BALB/C mice were subjected to chronic nicotine treatment (3.08mg/100ml in drinking water) for 4 weeks. Serum glucose, albumin, corticosterone and lipid profile levels were determined. Body weight changes were also monitored. We have found that nicotine treatment raises total cholesterol and glucose levels more in male as compared to female mice. Low density lipoprotein cholesterol (LDL-C) levels were increased by 35% (P<0.01) only in male mice. However rise in triglycerides were greater in females (28%) than males (21%) when compared with their respective controls. Serum albumin levels were increased in both sexes showing 13% greater increase in males as compared to females. However nicotine treatment had no effect on high density lipoprotein cholesterol, corticosterone levels and body weights in both genders. It is concluded that nicotine use is positively associated with LDL-C in males; the results are discussed in relation to prevalence of metabolic syndrome andrisk of cardiovascular events in nicotine users.